The application of graphic methods and the DEA in predicting the risk of bankruptcy - Róbert Štefko; Jarmila Horváthová; Martina Mokrišová (Journal of Risk and Financial Management, 2021)
The paper deals with the issue of analyzing the financial failure of businesses. The aim was to select key performance indicators entering the DEA model. The research was carried out on a sample of 343 Slovak heat management companies. When addressing the research problem, we made use of multidimensional scaling (MDS) and principal component analysis (PCA), which pointed out the areas of financial health of companies that may predict their financial failure. The core of our interest and research was the data envelopment analysis (DEA) method, which represents a more exact approach to the assessment of financial health. The important finding is that the statistical graphical methods - PCA and MDS - are very helpful in identifying outliers and selecting key performance indicators entering the DEA model. The benefit of the paper is the identification of companies that are at risk of bankruptcy using the DEA method. The originality is the selection of key inputs and outputs to the DEA model by the PCA method.
Keywords: 330; data envelopment analysis; financial distress; multidimensional scaling; prediction; principal component analysis; risk